Correlation between Students’ Habits in Listening to English Songs and Their Listening Skills of the Eleventh-Grade Students of SMA Negeri 6 Sigi - Natalia Lapuk; Mukrim Mukrim; Hastini Hastini (Journal of General Education and Humanities, 2023)
The objective of this research is to find out if there is any correlation between students' habits in listening to English songs and the listening skills of the eleventh-grade students of SMA Negeri 6 Sigi. This quantitative research applied a correlational research design. The researcher used simple random sampling. In this research, 32 students were chosen as the sample. The researcher gathered information through questionnaires and tests. Both instrument data analyses showed a Pearson Product Moment of 0.567. The Category was moderate. The value of the r-table was 0.349. rxy is more than rtable, according to the statistics. The alternative hypothesis (Ha) is accepted, while the null hypothesis (H0) is rejected. This indicates a correlation between students’ habits in listening to English songs and the listening skills of the eleventh-grade students at SMA Negeri 6 Sigi.